Greater Utilization of Neural-Circuits Related to Executive Functions is Associated with Better Reading: A Longitudinal fMRI Study Using the Verb Generation Task - Horowitz-Kraus, Tzipi; Vannest, Jennifer J.; Gozdas, Elveda; Holland, Scott K. (Frontiers in Human Neuroscience, 2014)
Introduction: Reading is an acquired- developmental ability that relies on intact language and executive function skills. Verbal fluency tasks (such as verb generation) also engage language and executive function skills. Performance of such tasks matures with normal language development, and is independent of reading proficiency. In this longitudinal fMRI study, we aim to examine the association between maturation of neural circuits supporting both executive functions and language (assessed using verb generation) with reading proficiency achieved in adolescence with a focus on left lateralization typical for language proficiency. Methods: Normalized fMRI data from the verb generation task was collected from sixteen healthy children at ages 7, 11 and 17 years and was correlated with reading scores at 17 years of age. Lateralization indices were calculated in key language, reading and executive function-related regions in all age groups. Results: Typical development was associated with (i) increasingly left lateralized patterns in language regions (ii) more profound left lateralized activation for reading and executive function-related regions when correlating with reading scores, (iii) greater involvement of frontal and parietal regions (in older children), and of the anterior frontal cortex (in younger children). Conclusions: We suggest that reading and verb generation share mutual neural-circuits during development with major reliance on regions related to executive functions and reading. The results are discussed in the context of the dual-networks architecture model.